1993
DOI: 10.1093/nar/21.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of nuclease resistant 3′ modified oligodeoxynucleotides

Abstract: An efficient chemical procedure for the immobilization of carboxylate containing conjugate groups onto controlled pore glass (CPG) is described. The derivatized supports were used in the automated synthesis of an oligodeoxynucleotide (20-mer ODN) containing a 3' phosphodiester linked hexanol, aminohexyl, acridine, or cholesterol group. The stability of the oligomer in a hepatoma cell culture was found to be prolonged two to three fold by the presence of any of the 3' tails. By contrast, an aminohexyl group app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 26 publications
(63 reference statements)
1
122
0
Order By: Relevance
“…It has been shown that oligonucleotides containing cholesterol adducts at the 3Ј-terminus are cytotoxic (41,42). Conjugation of the cholesterol group increases the cellular uptake of the antisense oligonucleotide and improves its nuclease resistance (43). Finally it has been demonstrated that the addition of a cholesterol group at the 5Ј-end of self-complementary oligonucleotides increases the stability of the duplex, probably via better stacking interactions with the terminal base pairs (44).…”
mentioning
confidence: 99%
“…It has been shown that oligonucleotides containing cholesterol adducts at the 3Ј-terminus are cytotoxic (41,42). Conjugation of the cholesterol group increases the cellular uptake of the antisense oligonucleotide and improves its nuclease resistance (43). Finally it has been demonstrated that the addition of a cholesterol group at the 5Ј-end of self-complementary oligonucleotides increases the stability of the duplex, probably via better stacking interactions with the terminal base pairs (44).…”
mentioning
confidence: 99%
“…It was next investigated whether fluorescently labeled alginate strands could home in vivo to a target gel through sequence-mediated targeting. ODNs were conjugated to alginate through the 3′ end to increase serum exonuclease stability (33)(34)(35). ODN-conjugated alginate strands were still competent to bind in a sequencespecific manner after 6 h, 12 h, and 24 h of circulation in the blood (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One challenge to this type of application is ODN stability. In this work alginate was conjugated to the 3′ end of ODNs to overcome 3′-5′ exonucleases (the major serum-based nuclease) (33)(34)(35) and the backbone was modified with phosphorothioate groups for increased endonuclease and chemical stability (46). These changes were sufficient to protect alginate strand-conjugated ODNs for up to 12 h in circulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphodiester oligonucleotides facing the medium were sensitive to degradation by DNase I at high concentrations (Fig. 1), but as they are coupled to cholesterol at their 3' extremity they should be protected to some extent against nucleases present in serum (Boutorine et al, 1992;Gamper et al, 1993) which are principally Y-exonucleases (Shaw et al, 1991).…”
Section: Discussionmentioning
confidence: 99%